Disease-related outcomes and toxicities of intensity modulated radiation therapy after lung-sparing pleurectomy for malignant pleural mesothelioma: a systematic review - Patel, Roshal R.; Ludmir, Ethan B.; Miccio, Joseph A.; Menon, Hari; Barsky, Andrew R.; Mesko, Shane M.; Kodali, Manya; Lautenschlaeger, Tim; Adeberg, Sebastian; Simone, Charles B.; Verma, Vivek (Practical Radiation Oncology, 2020)
Purpose - This review explores the use of intensity modulated radiation therapy (IMRT) after lung-sparing surgery in malignant pleural mesothelioma (MPM). Because severe toxicities have been documented after radiation therapy for MPM, its use remains controversial, especially as modern surgical management has shifted toward lung-sparing pleurectomy/decortication. IMRT is an advanced technique that may allow for safer radiation therapy delivery, but there remains limited data (including no summative data) to support this notion. - Methods and Materials - We performed a systematic review evaluating the safety and efficacy of post-pleurectomy IMRT (P-IMRT). A systematic review of PubMed using Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines was conducted for publications of all dates that specifically reported clinical outcomes and/or toxicities of P-IMRT in patients with MPM. Ten original studies were included in this review. - Results - The incidence of grade 3 pneumonitis ranged from 0% to 16%, with all but 2 studies reporting rates below 9%. Grade 4 and 5 pneumonitis were observed in less than 1.5% of cases, except in one publication that used hypofractionated radiation therapy to doses >60 Gy. Crude local failure rates ranged from 19% to 60%, median progression free survival ranged from 12 to 16 months, and median overall survival ranged from 19 to 28 months. - Conclusions - P-IMRT produces relatively few higher-grade toxicities and has reasonable disease-related outcomes, especially when delivered using conventionally fractionated regimens to doses of 45 to 54 Gy and exercising careful attention to dose constraints during treatment planning. IMRT can thus be considered in well-selected patients in whom adequate survival after pleurectomy is expected. These data also support the initiation of the phase III NRG-LU006 trial of extended pleurectomy/decortication and chemotherapy with or without IMRT.